If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 83 + -3x = 15x + 21 Reorder the terms: 83 + -3x = 21 + 15x Solving 83 + -3x = 21 + 15x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15x' to each side of the equation. 83 + -3x + -15x = 21 + 15x + -15x Combine like terms: -3x + -15x = -18x 83 + -18x = 21 + 15x + -15x Combine like terms: 15x + -15x = 0 83 + -18x = 21 + 0 83 + -18x = 21 Add '-83' to each side of the equation. 83 + -83 + -18x = 21 + -83 Combine like terms: 83 + -83 = 0 0 + -18x = 21 + -83 -18x = 21 + -83 Combine like terms: 21 + -83 = -62 -18x = -62 Divide each side by '-18'. x = 3.444444444 Simplifying x = 3.444444444
| 4w+2=18 | | 14-8x=89-29x | | -6x+6(-2x-12)=144 | | 2a^2+18a+28= | | 9x(2x+7)= | | 2345x-678=678 | | 5(3-2x)=75 | | 2x^2+13x=24 | | -496=-8(-10x-8) | | -165=5(5x-3) | | 5x+1=7+3x | | 160=-7x-6(2x+5) | | 4(5x+7)+-8=-16 | | 3(x-1)=3x+2 | | 8x+8=8x+12 | | 4r+15=4r+11 | | 4xy*6xy= | | -2(4x+5)-11=-5 | | 2x-2=x+x | | 23x-8-14x=10 | | 2(b+8)-9=9 | | 2x^2=-144 | | 3k^2-11k-20=0 | | (8x^3)(2)= | | -8b+9+6b=3b+14 | | (4xy)(6xy)= | | 1+7=43+x | | 234x-67=56 | | y-2=y+3 | | 4(5x-7)-8x=-5 | | 4xy+6xy= | | 6x+24=12x+14 |